Drilling the near Cortex with Elongated Figure-of-8 Holes to Reduce the Stiffness of a Locking Compression Plate Construct. (December 2015) - Chen, Jerry Yongqiang; Zhou, Zhihong; Ang, Benjamin Fu Hong; Yew, Andy Khye Soon; Chou, Siaw Meng; Chia, Shi-Lu; Koh, Joyce Suang Bee; Howe, Tet Sen
Purpose: To compare the stiffness of locking compression plate (LCP) constructs with or without drilling the near cortex with elongated figure-of-8 holes. Methods: 24 synthetic bones were sawn to create a 10-mm gap and were fixed with a 9-hole 4.5-mm narrow LCP. In 12 bones, the near cortex of the adjacent holes to the LCP holes was drilled to create elongated figure-of-8 holes before screw insertion. The stiffness of LCP constructs under axial loading or 4-point bending was assessed by (1) dynamic quasi-physiological testing for fatigue strength, (2) quasi-static testing for stiffness, and (3) testing for absolute strength to failure. Results: None of the 24 constructs had subcatastrophic or catastrophic failure after 10 000 cycles of fatigue loading (p=1.000). The axial stiffness reduced by 16% from 613±62 to 517±44 N/mm (p=0.012) in the case group, whereas the bending stiffness was 16±1 Nm 2 in both groups (p=1.000). The maximum axial load to catastrophic failure was 1596±84 N for the control group and 1627±48 N for the case group (p=0.486), whereas the maximum bending moment to catastrophic failure was 79±12 and 80±10 Nm, respectively (p=0.919). Conclusion: Drilling the near cortex with elongated figure-of-8 holes reduces the axial stiffness of the LCP construct, without compromising its bending stiffness or strength.